MASS FATALITY PREPAREDNESS ELEMENTS AMONGST AUTOPSY SURGEONS IN INDIA - Chauhan, M; Sreenivas , M; Khanna, SK; Chhoker, VK (Journal of Forensic Medicine and Toxicology, 2024)
Background: The present study assessed the managerial capabilities of autopsy surgeons in India in future response as preparedness to disaster. The need for this was further highlighted by various disasters or similar situations that have been witnessed by the mankind during the 21st century, including the ongoing Covid-19 pandemic, with its latest variant of concern “Omicron”. Aims and objectives: To provide literature related to mass fatality management related benchmarks, and correlates of actual preparedness as a response to a future disaster, and suggest action plan (if any) in the light of the results. Materials and Methods: This cross sectional study was conducted as an anonymous survey by utilizing a pre tested and validated self-administered questionnaire that was made available via electronic mail to the study Results: Maximum respondents were seen in the age group of 26-35 years. The commonest duration of experience ranged from 2-5 years after attaining post-graduate qualification. The commonest type of employment was contractual/adhoc basis. A significant majority of subjects did not receive any formal training in disaster mortuary response, and not even a single subject participated in a simulated real world disaster. Infection control policies were in place to the extent of 98%. All the subjects reported having up to date contact phone list for staff and key contacts. The formal arrangements of supplies and repair service providers needed to ensure the smooth functioning of mortuary services during a future disaster event was not up-to the mark. The written inventory of the key items was not updated in majority of the cases. All the respondents indicated the need of training programmes in routine for efficient management and disaster preparedness Conclusions: The current job position of the autopsy surgeon as a factor showed the strongest association with most of the key parameters related to mortuary preparedness elements.
Keywords: Disaster; mass fatality; autopsy surgeons; morgue services; management of dead